Femur Pathological Fracture Caused by Metastatic Bone Disease Derived from Foot Squamous Cell Carcinoma - Ferdiansyah .; Mouli Edward; Muhammad Hardian Basuki; Deny Mory Aryawan (Universitas Muhammadiyah Surabaya, 2017)
Background : Bone is an organ and the most common site that prone to metastatic cancer and cause serious morbidity. Besides, metastatic cancer to bone will limit skeletal function so that decrease quality of life and even death that most of them caused by its complication.Objective : Reporting a rare case about Squamous Cell Carcinoma that cause femur pathological fracture caused by Metastatic Bone Disease.Material and Method : Case report in women patients 55 years old with femur close fracture one-third middle caused by Metastatic Bone Disease in RSUD Soetomo Surabaya, period May 2015-March 2016.Data is taken retrospectively from medical record through interview, physical examination, radiological examination, and laboratory.Result and Discussion : Patients are treated in hospital because of femur close fracture one-third middle caused by Metastatic Bone Disease. Based on physical and radiological examination, it is decided being done by skin traction first. The next plan is surgery. Patients are treated with interlocking nail left femur. Evaluation after surgery is done with medical rehabilitation, that is ROM exercise. Until now, 9 months after surgery, patients still control routinely to be done chemotherapy and there is improvement in patient’s condition.Conclusion : Metastatic process in bone often cause pathological fracture. Bone Metastatic is common from Breast, Lung, Prostate and Kideney Cancer. There was no publication before about Bone Metastatic Disease come from Squamous Cell Cancer. Mirel’s score is used as guiding in fixation prior to the next treatment. Decision of surgery is considered through patient’s objective and subjective appraisal that can be calculated in Abdurrahman score system.